Proceedings of the Modern Physics of Compact Stars 2015 — PoS(MPCS2015) 2016
DOI: 10.22323/1.262.0018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strong magnetic fields on hybrid stars

Abstract: In this work we study the effects of strong magnetic fields on hybrid stars by using a full general-relativity approach, solving the coupled Maxwell-Einstein equation in a selfconsistent way. The magnetic field is assumed to be axi-symmetric and poloidal. We take into consideration the anisotropy of the energy-momentum tensor due to the magnetic field, magnetic field effects on equation of state, the interaction between matter and the magnetic field (magnetization), and the anomalous magnetic moment of the had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…where ε is the total energy density which is the sum of the matter energy density ε m and magnetic stress B 2 8π , P ⊥ and P are the perpendicular and parallel components of the total pressure with respect to the magnetic axis, P m is the matter pressure and MB is the magnetization. It has been previously shown [21,22,23] that the effect of landau quantization in the EoS is not significant for reasonable magnetic fields (although the magnetic field modifies significantly the central value of the EoS and population of the star [13]). The effect from magnetization can also as an approximation, be neglected.…”
Section: Deformation Due To Magnetic Fieldmentioning
confidence: 98%
See 1 more Smart Citation
“…where ε is the total energy density which is the sum of the matter energy density ε m and magnetic stress B 2 8π , P ⊥ and P are the perpendicular and parallel components of the total pressure with respect to the magnetic axis, P m is the matter pressure and MB is the magnetization. It has been previously shown [21,22,23] that the effect of landau quantization in the EoS is not significant for reasonable magnetic fields (although the magnetic field modifies significantly the central value of the EoS and population of the star [13]). The effect from magnetization can also as an approximation, be neglected.…”
Section: Deformation Due To Magnetic Fieldmentioning
confidence: 98%
“…The exact value of the magnetic field and its structure depend strongly on the region of the star in which the magnetic field is assumed to be found. This limit also needs to be calculated taking into account general relativity and magnetic field modifications in the metric, not to mention magnetic field modifications to the equation of state itself, which also has its central density substantially modified [13].…”
Section: Introductionmentioning
confidence: 99%
“…A model-dependent distance of 116 ± 16 pc has been reported for AR Sco and the mass of the WD is in the range of 0.81 − 1.29 M (Marsh et al 2016). By using the observations of luminosity, the rotation frequency and the frequency derivative of the WD, Franzon & Schramm (2016) found that the WD might have a mass close to 1.29 M and estimated its radius of ∼ 4080 km and the central and surface magnetic fields of ∼ 0.9 × 10 13 G and ∼ 8.95 × 10 11 G, respectively. The parameters mentioned above are important for understanding the physical processes on-going in AR Sco, unfortunately, due to the relatively large uncertainty of distance (13%), they can not be tightly constrained.…”
Section: Why We Need Parallax Measurement For Ar Sco?mentioning
confidence: 98%
“…Another aspect that will benefit from the distance determination is the amplitude estimation of the gravitational wave coming from AR Sco, the pulsing WD-MD binary system. Using the model-dependent distance of ∼ 116 pc, the gravitational wave amplitude for AR Sco was estimated to be ∼ 10 − (22−23) (Franzon & Schramm 2016), which might lead to a detectable signal by LIGO and VIRGO. By applying more precise distance, the gravitational wave amplitude from AR Sco can be tightly constrained, which would help to optimize detecting strategy for the gravitational wave detectors.…”
Section: Why We Need Parallax Measurement For Ar Sco?mentioning
confidence: 99%
“…Note, however, that this does not imply a conflict with the observed heavy stars, as the reduction of the stellar masses due to the condensation only takes place for strongly magnetized stars, when the magnetic field itself leads to an increase of the allowed star masses [24]. Recently, there has been discussion involving the systematics of calculations of neutron star radii of typical 1.4 solar mass stars.…”
Section: Pos(icpaqgp2015)009mentioning
confidence: 99%